Auditoría de gestión al cuerpo de bomberos del cantón Zamora a sus componentes recursos humanos e infraestructura período: enero – diciembre de 2015 - Guamán Guaillas, Yury Maribel (2017)
The investigative work was done as a prerequisite to the degree in Accounting and Auditing Engineering, in order to analyze whether the Human Resource that works in the institution performs with efficiency, effectiveness and effectiveness, as well as verify if the Infrastructure where The Zamora Fire Department operates, it is functional for the development of the bomberil activity. It is important to base the research with theoretical contents relevant to the subject and the type of entity such as Management Audit, Internal Control, and each of the phases: Previous Visit, Specific Planning with the Internal Control System Evaluation and the Matrix Decision-making process; The third phase is related to the Execution, where the field work is developed and the procedures for each component are applied and the findings found duly evidenced and supported in the working papers, the elaboration of narrative, summary and analytical data; The fourth phase is the communication of results that culminates in the presentation of the final report, which contains the cover letter, comments, conclusions, and recommendations; The fifth phase that is the follow-up of the recommendations. In order to establish compliance with the legal, regulatory and other applicable regulations implemented by the institution, and in order to determine or measure the degree of efficiency, effectiveness and effectiveness, the evaluation was performed through the Internal Control Questionnaire. The objective of the Management Audit was fulfilled, which is to review the efficiency, effectiveness and effectiveness of Human Resource performance, such as the functionality of the Infrastructure of the Fire Department of Zamora in the period January to December 2015, objective In which it was established that the strategic plan of the institution has been disseminated, the personnel have not been trained, there is insufficient control of the assistance of the staff of this institution, nor is there any control over the activities that Are performed; In relation to the Infrastructure component, it is determined that it is not functional for the development of the activities, there is no person in charge of the maintenance of the infrastructure and that it is used in activities other than those that were created. Among the conclusions reached is that through the Management Audit was able to have knowledge of the work of Human Resource, determining the lack of appropriate physical infrastructure for the development of its activities, so it is recommended to manage the construction of the Building for the institution, so that its servants can provide a service with efficiency and administrative efficiency.